The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/fst.05720
|View full text |Cite
|
Sign up to set email alerts
|

Use of natural substrates as an alternative for the prevention of microbial contamination in the food industry

Abstract: The use of additives by the food industry is a way to prevent bacterial and fungal contamination in products as well as to conserve foods during their shelf life, preventing them from causing diseases or undesirable alterations in the sensory characteristics of foods. Food producers are greatly concerned about decreasing the addition of synthetic compounds, to avoid harm to the consumer's health and to the environment and, at the same time, about contributing to the maintenance of a safe food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
3
0
1
Order By: Relevance
“…It could be produced by gram-positive and gram-negative bacteria. They are mostly used in the food industry as natural bio preservatives instead of chemical preservatives to protect products from spoilage and pathogenic bacteria (Todorov et al, 2019;Pato et al, 2022b;Barboza et al, 2022). Bacteriocins-like inhibitory substances (BLIS) are also ribosomally synthesized peptides that possess abilities like bacteriocin but have not been yet characterized for their amino acid sequence (Caulier et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It could be produced by gram-positive and gram-negative bacteria. They are mostly used in the food industry as natural bio preservatives instead of chemical preservatives to protect products from spoilage and pathogenic bacteria (Todorov et al, 2019;Pato et al, 2022b;Barboza et al, 2022). Bacteriocins-like inhibitory substances (BLIS) are also ribosomally synthesized peptides that possess abilities like bacteriocin but have not been yet characterized for their amino acid sequence (Caulier et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Hundreds of millions of people throughout the world are at danger of consuming contaminated food (Barboza et al, 2021;Ngafwan et al, 2021;Zhao & Talha, 2021). Every year, millions of people fall ill and hundreds of thousands die as a result of consuming tainted food.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted recently to produce foods with a safe microbiological standard and without synthetic preservatives. However, many studies are needed to prove that these substances are harmless to the worker's health, environment, and humans (Barboza et al, 2022). Thus, after analyzing the risk agents in an industrial kitchen, it was found that toxicological, biological, chemical, mechanics, and environmental risks are agents that the work team exposes daily.…”
Section: Introductionmentioning
confidence: 99%